INVESTIGATION OF THE EFFECT OF A HYBRID DRYING METHOD ON THE COLOR QUALITY OF NECTARINE SLICES AND ENERGY CONSUMPTION - DEMIREL, Fatmagül Mutlu; ISMAIL, Osman (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The main objective of a product quality study for drying agricultural products without causing distortion is to reduce the product moisture value to a final moisture value while expending the least energy and time. In the first stage of this study, nectarine slices were dried in a microwave and cabinet dryer under different drying conditions. Experiments in the microwave dryer were done at four different power levels: 90, 180, 360, and 600 W. Hot air drying was done at two temperatures, 50 and 70 °C, with a constant air velocity (2.0 m/s). In the second stage, after those experiments, the hybrid drying method were constructed based on the color parameter, and moisture ratio. In the hybrid drying method, hot air drying was carried out with microwave pretreatment. The most effective hybrid drying method in terms of optimal drying time, energy consumption, and color parameters was found to be at 180 W microwave power and 70 °C.